Reduced Expression of Voltage-Gated Sodium Channel Beta 2 Restores Neuronal Injury and Improves Cognitive Dysfunction Induced by Aβ1-42 - Shan Li; Guo-Ji Yan; Ya-Xin Tan; Lu-Lu Xue; Ting-Hua Wang; Hao-Ran Zhao; Min-Nan Lu; Hui-Xiang Zhang; Rong Mei; Xiao-Han Dong; Li-Na Liu; Dan Wang; et al. (Neural Plasticity)
Voltage-gated sodium channel beta 2 (Nav2.2 or Navβ2, coded by SCN2B mRNA), a gene involved in maintaining normal physiological functions of the prefrontal cortex and hippocampus, might be associated with prefrontal cortex aging and memory decline. This study investigated the effects of Navβ2 in amyloid-β 1-42- (Aβ1-42-) induced neural injury model and the potential underlying molecular mechanism. The results showed that Navβ2 knockdown restored neuronal viability of Aβ1-42-induced injury in neurons; increased the contents of brain-derived neurotrophic factor (BDNF), enzyme neprilysin (NEP) protein, and NEP enzyme activity; and effectively altered the proportions of the amyloid precursor protein (APP) metabolites including Aβ42, sAPPα, and sAPPβ, thus ameliorating cognitive dysfunction. This may be achieved through regulating NEP transcription and APP metabolism, accelerating Aβ degradation, alleviating neuronal impairment, and regulating BDNF-related signal pathways to repair neuronal synaptic efficiency. This study provides novel evidence indicating that Navβ2 plays crucial roles in the repair of neuronal injury induced by Aβ1-42 both in vivo and in vitro.